PERBEDAAN PENYULUHAN MENGGUNAKAN MEDIA VIDEO REKAMAN DAN VIDEO PRESENTAS TERHADAP TINGKAT PENGETAHUAN TENTANG CARA MENYIKAT GIGI DENGAN METODE BASS PADA SISWA USIA 13 TAHUN DI MADRASAH TSANAWIYAH MUHAMMADIYAH MARTAPURA - Reza, Reza; Rahman, Waljuni Astu; Rahmawati, Hj.Ida (JURNAL TERAPIS GIGI DAN MULUT, 2022)
One of the factors that cause high dental and oral health problems is tooth brushing behavior. Brushing behavior is influenced by knowledge about brushing teeth using the right technique or method. The media used in providing dental health education to children are video recordings and video presentations. In the video presentation, interaction with children can be carried out which can stimulate curiosity in children so that the dental health education material discussed can be well received by children. This study aims to determine the differences in counseling using recorded video media and video presentations on the knowledge of brushing teeth with the bass method on 13 year old students at Madrasah Tsanawiyah Muhammadiyah Martapura. This research is a quasi-experiment with a pretest posttest research design. The sampling technique was purposive sampling with a sample size of 30 students. The results of this study indicate that the average knowledge of using video recordings before counseling is 10.27 and after counseling is 13.00, while the average knowledge of using video presentations before counseling is 12.27 and after counseling is 13.60 based on statistical results with this test. Paired T-Test resulted in p value = 0.000 < = 0.05. Based on the results of the independent Simple T-Test, the value of p = 0.002 < = 0.05 was obtained. In conclusion, there are differences in counseling using recorded video media and video presentations on tooth brushing knowledge